TH17 cells in health and disease - Jiang, Shuiping (Springer New York, 2011)
About 25 years ago, Mosmann & Coffman introduced the TH1 / TH2 paradigm of T helper cell differentiation which helped explain many aspects of adaptive immunity from eliminating intracellular versus extracellular pathogens to induction of different types of tissue inflammation. However, TH1 / TH2 paradigm could not adequately explain development of certain inflammatory responses which provided impetus for the discovery of a new subset of T cells called TH17 cells. After the discovery of differentiation and transcription factors for TH17 cells, it was clear that TH17 cells represent an independent subset of T cells with specific functions in eliminating certain extracellular pathogens, presumably not adequately handled by TH1 or TH2 cells. The major role of TH17 cells has been described in inducing auto-immune tissue inflammation. The discovery of TH17 cells has expanded the TH1 / TH2 paradigm, and the integration of TH17 cells with TH1 and TH2 effector T cells is beginning to explain the underlying mechanisms of tissue inflammation in a number of infections and auto-immune disease settings. - From Chapter One by Vijay K. Kuchroo, Harvard University, USA. The recently identified Interleukin 17 (IL-17) cytokine family contributes to immunity to infectious diseases and chronic inflammatory diseases. Further studies on the regulation and function of this important cytokine family may provide better understanding on the roles of the IL-17 family in immune-mediated diseases; such knowledge may lead to the development of immunotherapeutic strategies for treatment of several inflammatory diseases. - From Chapter Two by Chen Dong, University of Texas and MD Anderson Cancer Center, USA.